Bromide ion mediated modification to digestive ripening process: preparation of ultra-small Pd, Pt, Rh and Ru nanoparticles - Seth, Jhumur; Bhagavatula L. V. Prasad (Nano Research, 2016)
Nanoparticles of catalytically important transition metals, such as Pd, Pt, Rh, and Ru have been prepared by the well-known “digestive ripening” (DR) and “modified digestive ripening” (mDR) methods. In the traditional DR process, a polydisperse colloidal dispersion is refluxed in the presence of a surface-active molecule, such as alkanethiol. The mDR method involved a small modification in the procedure, wherein refluxing was performed with an alkanethiol and a tetra-alkylammonium bromide surfactant. This minor modification led to a dramatic change in the final particle size distributions, giving access to nanoparticles in the <3 nm size regime; this was not possible with the traditional DR process. Bromide ions, which are present during refluxing, proved to be an important ingredient in the modification process. These bromide ions are revealed to act as etchants, resulting in ultra-small nanoparticles. All transition metal nanoparticles investigated displayed catalytic activity in the reduction reaction of p-nitro phenol. Pd nanoparticles, synthesized by a modified digestive ripening method, exhibited the best catalytic activity among the systems investigated.